Does Tiktok and Instagram Affect Brand Awareness? Empirical Study on Asiacommerce Companies - Yudha, Aji; Norsiva, Rifki Irham; Lestari, Lela; Yasmin, Annisa (Asian Journal of Logistics Management, 2024)
This study is a qualitative descriptive research aimed at describing the use of social media to increase brand awareness for AsiaCommerce on Instagram and TikTok. The data collection methods used in this research include observation, interviews, and documentation. The results indicate that the social media activities on these platforms have significantly increased AsiaCommerce's brand awareness, reaching hundreds of thousands of potential clients. However, the activities have not always met the key performance indicator (KPI) targets due to factors such as content delivery adjustments, limited demographic targeting, difficulty in appealing to the audience, and keeping up with changing trends. To maximize brand awareness, strategic efforts such as giveaways, advertisements, key opinion leader (KOL) strategies, live marketing, and the use of artificial intelligence (AI) for content creation have been implemented. This research has practical implications for social media applications.